Effects of Phonological Training on the Reading and Reading-Related Abilities of Hong Kong Children with Dyslexia - Wang, Li-Chih (Frontiers in Psychology, 2017)
This study aimed to investigate phonological awareness training by examining outcomes among Chinese children who learn Chinese without phonetic system training. Fifty-six Hong Kong children from the 3rd to 6th grades were recruited. Two-thirds of the children had been officially identified as dyslexic by the local government, and the remainder were considered high risk for dyslexia. The children were divided equally into a control group and an experimental group, with the groups matched as closely as possible by age and gender. Children in the experimental group were trained by onset-rime-level phonological training. The training lasted approximately three weeks, with 15 daily sessions lasting approximately 20 minutes each. Our results indicated that children in the experimental group made significant improvements in Chinese character reading, onset awareness, rime awareness, and rapid naming after training. The association between phonological awareness and Chinese character reading, especially the association between rime awareness and Chinese character reading, also changed after training. The benefits of phonological awareness training were more obvious for children younger than ten years old. The results of the present study can be extended to provide another approach to Chinese learning for children suffering from reading difficulties who are not responding to the usual approach in their region.